Assessment Of Problems Associated With Engineering Assets Management Practices In Food Manufacturing Companies In Nigeria - Ilori, O. O.; Adeniyi, A. A.; Akanbi, C.T. (Ife Journal of Technology, 2010)
Asset management offers a systematic approach to realizing the extent of the problem and providing a mechanism for improvement. This paper assessed the problems associated with engineering assets management (EAM) practices in small and medium-scale food manufacturing companies in Nigeria. Data were collected using questionnaire from selected 30 food manufacturing companies registered with National Agency for Food and Drug Administration and Control (NAFDAC), in the study area. The questionnaire was administered on top officials in the companies. The data were analyzed using both descriptive and inferential statistics. The study has shown that several activities and practices involved in the food manufacturing companies were error-provoking and are impediments to a better management of engineering assets. Factors that caused engineering assets failures (downtime) in food companies include; equipment design, purchase, storage (inventory), installation, and operation and maintenance. However, priorities should be placed on the fundamentals of asset management, that is, understanding and defining the level of service. Also, more efforts should be put in staff development in order to expand their knowledge and skills of maintenance staffs in specialized areas of engineering assets management practices.